2018
DOI: 10.1021/acssuschemeng.8b00449
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Salt as Catalyst for Direct Synthesis of Carbamate from Carbon Dioxide

Abstract: Carbamates are an important motif in agricultural chemistry, medicinal chemistry, and polyurethane preparation. Potassium carbonate (K2CO3) is a common, nontoxic, and inexpensive chemical and is widely used in organic synthesis. Herein we report the use of K2CO3 as a catalyst for direct synthesis of carbamate from amine, silicate ester, and carbon dioxide. Especially, both alkyl amines and aromatic amines could be activated, largely expanding the substrate scope compared with the use of alcohol as the coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 72 publications
(82 reference statements)
0
27
0
Order By: Relevance
“…MPC could be synthesized via the reactions of phenylurea and dimethyl carbonate (DMC) 4 and/or methanol, 5 aniline and DMC 2,6-10 and/or methyl carbamate (MC), 3,11 and even aniline and C 1 source (e.g. CH 3 OH and CO 2 ), [12][13][14] etc. And some new synthetic paths have also been developed recently.…”
Section: Introductionmentioning
confidence: 99%
“…MPC could be synthesized via the reactions of phenylurea and dimethyl carbonate (DMC) 4 and/or methanol, 5 aniline and DMC 2,6-10 and/or methyl carbamate (MC), 3,11 and even aniline and C 1 source (e.g. CH 3 OH and CO 2 ), [12][13][14] etc. And some new synthetic paths have also been developed recently.…”
Section: Introductionmentioning
confidence: 99%
“…A proposed mechanism was outlined in Scheme . First, Cs 2 CO 3 binds with aniline and extracts a proton from it . Then the carboxylation of amine by CO 2 takes place to produce intermediate C .…”
Section: Methodsmentioning
confidence: 99%
“…First, Cs 2 CO 3 binds with aniline and extracts a proton from it. [19] Then the carboxylation of amine by CO 2 takes place to produce intermediate C. Afterward, intermediate C sequentially releases Ts À and N 2 under the assistance of base, leading to carbene intermediate D. Finally, intramolecular insertion of carboxylic to carbene delivers 1,4-dihydro-2H-3,1-benzoxazin-2ones (3 a).…”
mentioning
confidence: 99%
“…In 2017 and 2018, Choi and co‐workers developed a more environmentally friendly carbamate synthesis by replacing a zinc catalyst with an ionic liquid [30a–c] . Having first reported an efficient synthesis by using Zn(OAc) 2 , [30a] they later found that ionic liquids could replace the transition metal catalyst.…”
Section: Synthesis Of Acyclic Carbamatesmentioning
confidence: 99%